Applications of homochiral metal‐organic frameworks in enantioselective adsorption and chromatography separation. Issue 19 (19th May 2014) - Li, Xianjiang; Chang, Cuilan; Wang, Xin; Bai, Yu; Liu, Huwei; Chankvetadze, Bezhan
<x xml:space="preserve">Abstract</x> Chiral separation is of great importance for drug development, pharmacology, and biology. Chiral metal‐organic frameworks (MOFs) is a new class of porous solid materials with high surface area, large pore size, high chemical stability, uniformly structured cavities, and the availability of modification. The excellent properties of MOFs have attracted intense interest to explore their performance and mechanism in chiral separation. This review summarizes three synthetic strategies of chiral MOFs and their applications in enantioselective adsorption and chromatographic separation. All the experimental and molecular simulation results demonstrated that high enantioselectivity was strongly correlated with a close match between the size of the pore and chiral molecules.